Method for estimating iron content of product in a porous carbon material refining process
Patent Information
- Application Number
- CN202311181311.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-09-14
AI Technical Summary
[0008]本发明的目的就是针对现有技术无法在多孔碳材料精制过程中预估产物铁含量的缺陷,而提供一种能够在精制步骤过程中预估精制产物的铁元素含量且与真实值十分贴近,以便于及时调控精制工艺使产品中铁含量符合要求的多孔碳材料精制过程中预估产物铁含量的方法
[0056](1)可以在精制步骤过程中预估精制产物的铁元素含量,以便于提高品控。同时也避免了在精制完成后发现铁含量不符合要求,重新精制过程带来的资源、能源和时间的浪费以及废气废水排放量的增加;
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of porous carbon material production, specifically to a method for predicting the iron content in the product during the refining process of porous carbon materials, which is used to guide and control the iron content of the refined porous carbon material product. Background Technology
[0002] Porous carbon, including activated carbon, super-activated carbon, and carbon aerogel, is a general term for carbon materials prepared from carbon-containing raw materials such as biomass, coal, petroleum coke, or resin through carbonization and activation processes. It possesses a well-developed pore structure (containing numerous micropores and mesopores) and a large specific surface area (typically between 1000 and 2300 m²). 2 It has excellent properties such as being within the range of / g and having strong adsorption capacity (iodine adsorption value is usually between 400 and 2000 mg / g).
[0003] Porous carbon has a wide range of applications. It can be used to purify air and water by adsorption, improve the specific capacity and volumetric capacity of supercapacitors by its high specific surface area, and deposit silicon into the pores through special processes to obtain silicon-carbon, the negative electrode material of batteries.
[0004] However, when applying porous carbon to energy storage applications such as capacitors and batteries, the purity requirements become more stringent, especially regarding the presence of metallic elements. High concentrations of metallic elements can negatively impact charging, discharging, and storage. For example, resin carbon is theoretically extremely pure during synthesis, without any introduced impurities. However, in the carbon activation process, the high-temperature environment inevitably introduces metallic elements, predominantly iron, into the product. Therefore, refining processes are essential to obtaining high-purity porous carbon.
[0005] GB / T 37389 mentions that the method for detecting trace metal elements in activated carbon for capacitors can use the inductively coupled plasma atomic emission spectrometry (ICP-AES) method in GB / T 24533. This method is advantageous due to its high accuracy, but the equipment is expensive. Many battery manufacturers, capacitor manufacturers, and porous carbon manufacturers also choose to use spectrophotometers to detect iron. The general steps of this method are: first, the iron or iron oxides in the porous carbon are completely dissolved by boiling in hydrochloric acid; after filtration, the supernatant is obtained; then, referring to the method for determining total iron in wastewater using the o-phenanthroline spectrophotometric method, the iron content of the porous carbon is calculated. The advantages of this method are a short testing cycle and low equipment cost.
[0006] However, in industrial production, both methods can only test the iron content in the porous carbon product obtained after refining. If the iron content exceeds the standard and does not meet the requirements, at best, rework and refining will be required, which will consume time, resources and energy. At worst, the entire batch of porous carbon products will be discarded and cannot be used, which will bring considerable economic losses to porous carbon manufacturers.
[0007] Therefore, it is particularly important to estimate the iron content of the product during the refining process of porous carbon materials and to adjust it in a timely manner. Summary of the Invention
[0008] The purpose of this invention is to address the shortcomings of existing technologies that cannot predict the iron content of products during the refining process of porous carbon materials. Instead, it provides a method for predicting the iron content of products during the refining process of porous carbon materials, which can accurately predict the iron content of the refined product during the refining step and closely approximate the actual value. This allows for timely adjustment of the refining process to ensure that the iron content in the product meets the requirements.
[0009] To achieve the above-mentioned objectives of this invention, a method for estimating the iron content of products during the refining process of porous carbon materials is provided, employing the following technical solution:
[0010] 1) Instrument preparation: UV-Vis spectrophotometer, analytical balance with an accuracy of 0.01%;
[0011] 2) Reagent preparation: Analytical grade reagents for acid etching agent, pH buffer, reducing agent, colorimetric agent and Fe standard solution;
[0012] 3) Sample preparation: Mix the porous carbon before purification evenly, and take 1.0000±0.0010g of sample from it; take 2.50mL of iron-containing wastewater from the purification process;
[0013] 4) Construction of standard curve: Prepare solutions of different concentrations by controlling the amount of Fe standard solution, add pH buffer, reducing agent and color developing agent to obtain solutions of different color intensities, use UV-Vis spectrophotometer to measure the absorbance of different color intensities of the solution to light at a wavelength of 510nm, and construct standard curve.
[0014] 5) Detection of porous carbon samples before purification: The porous carbon sample obtained in step (3) is fully reacted in an acid etchant, and the liquid phase is completely separated. A pH buffer, reducing agent, and colorimetric agent are added. The transmittance of light at a wavelength of 510 nm is measured using a UV-Vis spectrophotometer. The iron content C in the porous carbon sample before purification is calculated. 精制前 ;
[0015] 6) Detection of iron-containing wastewater samples: The iron-containing wastewater samples obtained in step (3) are further separated to obtain liquid phase components. pH buffer, reducing agent, and colorimetric agent are added. The transmittance of light at a wavelength of 510 nm is measured using a UV-Vis spectrophotometer. The iron content C in the iron-containing wastewater samples is calculated. 废液 ;
[0016] 7) Estimating the iron content of porous carbon samples: [The text abruptly ends here, likely due to an incomplete sentence or missing information.] 精制前 Multiply by the total mass of feed material in the refining process (m) 多孔碳 Then divide by the water consumption for the refining process (m). 水 The theoretical value C of the iron content in the iron-containing wastewater was obtained. 废液理论 ; with C 废液理论 Divide by C 废液 The ratio is obtained and denoted as the solubility ratio x; the iron content in the purified porous carbon sample is denoted as C. 精制后 Divide by C 精制前 The obtained ratio is the residual ratio y; multiply the solubility ratio x by the correction factor m and add the correction factor n to calculate the residual ratio y, and then calculate c. 精制后 Estimated value:
[0017] x = c 废液 / c 废液理论
[0018] y = mx + n
[0019] c 精制后 =yc 精制前
[0020] Furthermore, the etching agent is 3.7% hydrochloric acid, and the pH buffer is a mixed solution of 6.4% sodium acetate and 8.4% acetic acid.
[0021] Furthermore, the reducing agent is 1.0% hydroxylamine hydrochloride, and the colorimetric agent is 0.55% o-phenanthroline.
[0022] Furthermore, the Fe standard solution is a 0.007 mg / mL ferrous ammonium sulfate hexahydrate solution.
[0023] As a preferred embodiment of the present invention, step 4) is specifically as follows:
[0024] (i) Take 0 mL, 2 mL, 4 mL, 6 mL and 8 mL of 0.007 mg / mL ferrous ammonium sulfate hexahydrate respectively and add them to five 50 mL volumetric flasks;
[0025] (ii) Measure 5.00 mL of pH buffer, 2.50 mL of reducing agent and 1.00 mL of colorimetric reagent into each of the five volumetric flasks, make up to volume, mix well and let stand for 5-15 min.
[0026] (iii) The absorbance A at a wavelength of 510 nm was measured using a UV-Vis spectrophotometer, with the amount of iron standard solution used being V. 标准 Plot a standard curve with absorbance A on the x-axis and absorbance A on the y-axis, and fit the formula:
[0027] A = kV 标准 +b
[0028] A - Absorbance
[0029] V 标准 —Amount of iron standard solution used, mL
[0030] k—Slope of the standard curve
[0031] b—Standard curve intercept
[0032] As a preferred embodiment of the present invention, step 5) specifically involves the following steps:
[0033] (iv) Place the pre-refined porous carbon sample obtained in step (3) in 25.0 mL of acid etchant and react fully. Separate the solid and liquid phases by filtration and retain all liquid phase components. Dilute to 100 mL in a volumetric flask and keep for later use.
[0034] (v) Add 5.00 mL of pH buffer, 2.50 mL of reducing agent and 1.00 mL of colorimetric reagent to two 50 mL volumetric flasks in sequence. Take 10.00 mL of the solution from the 100 mL volumetric flask in step (iv) and add it to one of the 50 mL volumetric flasks. Make up to volume, mix well and let stand for 5-15 min. This is the experimental sample. Make up to volume in the other volumetric flask, mix well and let stand for 5-15 min. This is the reference sample.
[0035] (vi) The transmittance T at a wavelength of 510 nm was measured using a UV-Vis spectrophotometer. The transmittance T of the reference sample in step (v) was taken as 100, and the transmittance at opacity was taken as 0. The transmittance of the test sample in step (v) was then measured, and the iron content c of the porous carbon sample before purification was calculated using the formula. 精制前 :
[0036] A = log 10 (1 / T)+2
[0037] c 精制前 =(Ab) / k*100
[0038] A - Absorbance
[0039] k—Slope of the standard curve
[0040] b—Standard curve intercept
[0041] T - Transmittance
[0042] c 精制前 —Iron content, ppm
[0043] As a preferred embodiment of the present invention, step 6) specifically involves the following steps:
[0044] (vii) Separate the liquid phase components with unchanged concentration from the iron-containing wastewater sample obtained in step (3) by means of filtration, natural sedimentation or centrifugation;
[0045] (viii) Add 5.00 mL of pH buffer, 2.50 mL of reducing agent and 1.00 mL of colorimetric reagent to two 50 mL volumetric flasks in sequence. Take 2.50 mL of the liquid phase component from the 100 mL volumetric flask in step (vii) and add it to one of the 50 mL volumetric flasks. Make up to volume, mix well and let stand for 5-15 min. This is the experimental sample. Make up to volume in the other volumetric flask, mix well and let stand for 5-15 min. This is the reference sample.
[0046] (ix) Measure the transmittance T at a wavelength of 510 nm using a UV-Vis spectrophotometer. Using the transmittance T of the reference sample in step (viii) as 100 and the transmittance at opacity as 0, measure the transmittance of the test sample in step (viii), and calculate the iron content c in the iron-containing wastewater sample using the formula. 废液 :
[0047] A = log 10 (1 / T)+2
[0048] c 废液 =(Ab) / k*4
[0049] A - Absorbance
[0050] k—Slope of the standard curve
[0051] b—Standard curve intercept
[0052] T - Transmittance
[0053] c 废液 —Iron content, ppm
[0054] As a preferred embodiment of the present invention, the specific steps of step 6) are as follows: in step 7), the correction coefficient m is -0.4346 and the correction coefficient n is 0.6269.
[0055] Compared with existing technologies, the method for predicting the iron content of products during the refining process of porous carbon materials of the present invention has the following advantages:
[0056] (1) The iron content of the refined product can be estimated during the refining process, which can help improve quality control. It also avoids the waste of resources, energy and time, as well as the increase in waste gas and wastewater discharge, caused by the refining process after the iron content is found to be unacceptable after refining.
[0057] (2) The instruments required in this invention are only a UV-Vis spectrophotometer, an analytical balance (1 / 10,000), and the glassware mentioned above, which avoids the use of expensive equipment such as inductively coupled plasma atomic emission spectrometers and is easier to promote and use in actual industrial production.
[0058] (3) When measuring iron content using ultraviolet-visible spectrophotometry, the slope and intercept obtained from the fitted standard curve are only applicable to the range near the iron concentration at the time the standard curve was plotted. When the iron content of the measured object exceeds this range, the test results show a large deviation. This invention summarizes correction coefficients m and n based on a large amount of data from actual production, making the calculated c... 精制后 It is closer to the true value;
[0059] (4) In actual production, the correction coefficients can be fine-tuned based on a large amount of real data to make the estimation results more stable and accurate. Detailed Implementation
[0060] To describe the present invention, the following detailed description, in conjunction with embodiments, provides a method for estimating the iron content of products during the refining process of porous carbon materials, but this is not intended to limit the present invention.
[0061] Example 1
[0062] This invention provides a method for estimating the iron content of products during the refining process of porous carbon materials, comprising the following raw materials:
[0063] Acid etchant, pH buffer, reducing agent, colorimetric agent, and Fe standard solution.
[0064] The etching agent used was 3.7% hydrochloric acid, the pH buffer was a mixed solution of 6.4% sodium acetate and 8.4% acetic acid, the reducing agent was 1.0% hydroxylamine hydrochloride, the colorimetric agent was 0.55% o-phenanthroline, and the Fe standard solution was 0.007 mg / mL ferrous ammonium sulfate hexahydrate solution.
[0065] This invention provides a method for estimating the iron content of products during the refining process of porous carbon materials, comprising the following steps:
[0066] (1) Instrument preparation: UV-Vis spectrophotometer, analytical balance (0.01%);
[0067] (2) Reagent preparation: 3.7% hydrochloric acid, a mixed solution of 6.4% sodium acetate and 8.4% acetic acid, 1.0% hydroxylamine hydrochloride, 0.55% o-phenanthroline and 0.007 mg / mL ferrous ammonium sulfate hexahydrate solution;
[0068] (3) Sample preparation: Mix the porous carbon before refining evenly and take 1.0000±0.0010g of sample from it; take 2.50g of iron-containing wastewater from the refining process;
[0069] (4) Construction of standard curve: Prepare solutions of different concentrations by controlling the amount of ferrous ammonium sulfate hexahydrate solution. Add 5.00 mL of a mixed solution of 6.4% sodium acetate and 8.4% acetic acid, 2.50 mL of 1.0% hydroxylamine hydrochloride and 1.00 mL of 0.55% o-phenanthroline to obtain solutions of different color intensities. Use a UV-Vis spectrophotometer to measure the absorbance of different color intensities of the solutions to light at a wavelength of 510 nm and construct a standard curve.
[0070] (5) Detection of porous carbon samples before purification: The porous carbon sample obtained in step (3) was fully reacted in an acid etching agent, and the liquid phase was completely separated. 5.00 mL of a mixed solution of 6.4% sodium acetate and 8.4% acetic acid, 2.50 mL of 1.0% hydroxylamine hydrochloride, and 1.00 mL of 0.55% o-phenanthroline were added. The transmittance of light at a wavelength of 510 nm was measured using a UV-Vis spectrophotometer. The iron content c in the porous carbon sample before purification was calculated. 精制前 ;
[0071] (6) Detection of iron-containing wastewater samples: The iron-containing wastewater sample obtained in step (3) was further separated to obtain liquid components. 5.00 mL of a mixed solution of 6.4% sodium acetate and 8.4% acetic acid, 2.50 mL of 1.0% hydroxylamine hydrochloride, and 1.00 mL of 0.55% o-phenanthroline were added. The transmittance of light at a wavelength of 510 nm was measured using a UV-Vis spectrophotometer. The iron content c in the iron-containing wastewater sample was calculated. 废液 ;
[0072] (7) Prediction of porous carbon samples: c 精制前 Multiply by the total mass of feed material in the refining process (m) 多孔碳 Then divide by the water consumption for the refining process (m). 水 The theoretical value c of the iron content in the iron-containing wastewater was obtained. 废液理论 With c 废液理论 Divide by c 废液 The ratio is obtained and denoted as the solubility ratio x. The iron content in the purified porous carbon sample is denoted as c. 精制后 Divide by c 精制前The obtained ratio is the residual ratio y. Multiply the dissolution ratio x by the correction factor m = -0.4346 and add the correction factor n = 0.6269 to calculate the residual ratio y, and then calculate c. 精制后 The estimated value.
[0073] x = c 废液 / c 废液理论
[0074] y = mx + n
[0075] c 精制后 =yc 精制前
[0076] Examples 2, 3, 4, 5, and 6
[0077] The reagents and procedures were the same as in Example 1, except that the porous carbon before purification and the iron-containing wastewater during the purification process were taken from different purification batches. Relevant data are shown in Table 1:
[0078] Table 1
[0079]
[0080]
[0081] In the table above, c 精制前 c is measured in step (5) of each embodiment. 废液 c is measured in step (6) of each embodiment. 废液理论 Solubility ratio x, residual ratio y, and c 精制后 This is the result calculated in step (7) of each embodiment. 精制后实际值 The actual measurements of the refined batches sampled for each embodiment were obtained after refining.
[0082] This table demonstrates that the iron content c of the porous carbon after purification, obtained according to the estimation method provided by this invention, is... 精制后 , and the true value c 精制后实际值 Although there are differences, they are small and can provide guidance for refining processes in actual production.
Claims
1. A method for predicting the iron content of products during the refining process of porous carbon materials, characterized in that... The following technical solution is adopted: 1) Instrument preparation: UV-Vis spectrophotometer, analytical balance with an accuracy of 0.01%; 2) Reagent preparation: Analytical grade reagents for acid etching agent, pH buffer, reducing agent, colorimetric agent and Fe standard solution; 3) Sample preparation: Mix the porous carbon before purification evenly, and take 1.0000±0.0010 g of sample from it; take 2.50 mL of iron-containing wastewater from the purification process; 4) Construction of standard curve: Prepare solutions of different concentrations by controlling the amount of Fe standard solution, add pH buffer, reducing agent and color developing agent to obtain solutions with different color intensities, use a UV-Vis spectrophotometer to measure the absorbance of different color intensities of the solutions to light at a wavelength of 510 nm, and construct a standard curve. 5) Detection of porous carbon samples before purification: The porous carbon sample obtained in step (3) is fully reacted in an acid etchant, and the liquid phase is completely separated. A pH buffer, reducing agent, and colorimetric agent are added. The transmittance of light at a wavelength of 510 nm is measured using a UV-Vis spectrophotometer. The iron content C in the porous carbon sample before purification is calculated. 精制前 ; 6) Detection of iron-containing wastewater samples: The iron-containing wastewater samples obtained in step (3) are further separated to obtain liquid phase components. pH buffer, reducing agent, and colorimetric agent are added. The transmittance of light at a wavelength of 510 nm is measured using a UV-Vis spectrophotometer. The iron content C in the iron-containing wastewater samples is calculated. 废液 ; 7) Estimating the iron content of porous carbon samples: [The text abruptly ends here, likely due to an incomplete sentence or missing information.] 精制前 Multiply by the total mass of feed material in the refining process (m) 多孔碳 Then divide by the water consumption for the refining process (m). 水 The theoretical value C of the iron content in the iron-containing wastewater was obtained. 废液理论 ; with C 废液理论 Divide by C 废液 The ratio is obtained and denoted as the solubility ratio x; the iron content in the purified porous carbon sample is denoted as C. 精制后 Divide by C 精制前 The obtained ratio is the residual ratio y; multiply the solubility ratio x by the correction factor m and add the correction factor n to calculate the residual ratio y, and then calculate c. 精制后 Estimated value: 。 2. The method for estimating the iron content of products during the refining process of porous carbon materials as described in claim 1, characterized in that: The etching agent is 3.7% hydrochloric acid, and the pH buffer is a mixed solution of 6.4% sodium acetate and 8.4% acetic acid.
3. The method for estimating the iron content of products during the refining process of porous carbon materials as described in claim 2, characterized in that: The reducing agent is 1.0% hydroxylamine hydrochloride, and the colorimetric agent is 0.55% o-phenanthroline.
4. A method for estimating the iron content of products during the refining process of porous carbon materials as described in claim 1, 2, or 3, characterized in that: The Fe standard solution is a 0.007 mg / mL ferrous ammonium sulfate hexahydrate solution.
5. The method for estimating the iron content of products during the refining process of porous carbon materials as described in claim 4, characterized in that... The specific steps for step 4) are as follows: (i) Take 0 mL, 2 mL, 4 mL, 6 mL and 8 mL of 0.007 mg / mL ferrous ammonium sulfate hexahydrate respectively and add them to five 50 mL volumetric flasks; (ii) Measure 5.00 mL of pH buffer, 2.50 mL of reducing agent and 1.00 mL of colorimetric reagent into each of the five volumetric flasks, make up to volume, mix well and let stand for 5-15 min; (iii) The absorbance A at a wavelength of 510 nm was measured using a UV-Vis spectrophotometer, with the amount of iron standard solution used being V. 标准 Plot a standard curve with absorbance A on the x-axis and absorbance A on the y-axis, and fit the formula: A - Absorbance —Amount of iron standard solution used, mL k—Slope of the standard curve b—Standard curve intercept.
6. The method for estimating the iron content of products during the refining process of porous carbon materials as described in claim 5, characterized in that... The specific steps for step 5) are as follows: (iv) The porous carbon sample obtained in step (3) was placed in 25.0 mL of acid etching agent and reacted fully. The solid and liquid phases were separated by filtration, and all liquid phase components were retained. The sample was then diluted to 100 mL in a volumetric flask and kept for later use. (v) Add 5.00 mL of pH buffer, 2.50 mL of reducing agent and 1.00 mL of colorimetric reagent to two 50 mL volumetric flasks in sequence. Take 10.00 mL of the solution from the 100 mL volumetric flask in step (iv) and add it to one of the 50 mL volumetric flasks. Make up to volume, mix well and let stand for 5-15 min. This is the experimental sample. Make up to volume in the other volumetric flask, mix well and let stand for 5-15 min. This is the reference sample. (vi) The transmittance T at a wavelength of 510 nm was determined using a UV-Vis spectrophotometer. The transmittance T of the reference sample in step (v) was taken as 100, and the transmittance when opaque was taken as 0. The transmittance of the test sample in step (v) was measured, and the iron content c of the porous carbon sample before purification was calculated using the formula. 精制前 : A - Absorbance k—Slope of the standard curve b—Standard curve intercept T - Transmittance —Iron content, ppm.
7. The method for estimating the iron content of products during the refining process of porous carbon materials as described in claim 6, characterized in that, The specific steps for step 6) are as follows: (vii) The iron-containing wastewater sample obtained in step (3) is separated into liquid phase components with unchanged concentration by means of filtration, natural sedimentation or centrifugation; (viii) Add 5.00 mL of pH buffer, 2.50 mL of reducing agent and 1.00 mL of colorimetric reagent to two 50 mL volumetric flasks in sequence. Take 2.50 mL of the liquid phase component from the 100 mL volumetric flask in step (vii) and add it to one of the 50 mL volumetric flasks. Make up to volume, mix well and let stand for 5-15 min. This is the experimental sample. Make up to volume in the other volumetric flask, mix well and let stand for 5-15 min. This is the reference sample. (ix) The transmittance T at a wavelength of 510 nm was determined using a UV-Vis spectrophotometer. The transmittance T of the reference sample in step (viii) was taken as 100, and the transmittance at opacity was taken as 0. The transmittance of the test sample in step (viii) was then measured, and the iron content c in the iron-containing wastewater sample was calculated using the formula. 废液 : A - Absorbance k—Slope of the standard curve b—Standard curve intercept T - Transmittance —Iron content, ppm.
8. The method for estimating the iron content of products during the refining process of porous carbon materials as described in claim 7, characterized in that, The specific steps of step 6) are as follows: In step 7), the correction coefficient m is -0.4346 and the correction coefficient n is 0.6269.
Citation Information
Patent Citations
Preparation method of impurity element silver standard sample
CN115046830A